2018
DOI: 10.1159/000488265
|View full text |Cite
|
Sign up to set email alerts
|

C/D-Box Snord105b Promotes Tumorigenesis in Gastric Cancer via ALDOA/C-Myc Pathway

Abstract: Background/Aims: Small nucleolar RNAs (snoRNAs) play an important role in carcinogenesis. In this study, we identified a C/D box snoRNA, snord105b, and further investigated the function and mechanism of the snord105b in gastric cancer (GC). Methods: The expression level of snord105b in GC tissures, sera and cell lines were detected by qRT-PCR. Cell viability was assessed using MTS assay. Transwell and wound healing assay were performed to evaluate migration and invasion, and protein expression was examined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 27 publications
3
17
0
Order By: Relevance
“…( 25 ) Previous studies have found that ALDOA was highly expressed in lung cancer, pancreatic cancer, and gastric cancer. ( 37 , 38 , 39 ) Hu et al showed that the activity of ALDOA was increased under stimulation of phosphoinositide 3‐kinase–dependent activation of Rac by releasing filamentous actin‐bound ALDOA, linking actin remodeling to glycolysis. ( 40 ) Overexpression of ALDOA promoted formation of a cancer‐associated proton pump inhibitor with γ‐actin and accelerated lung cancer metastasis, ( 37 ) suggesting its role as an oncogene in tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…( 25 ) Previous studies have found that ALDOA was highly expressed in lung cancer, pancreatic cancer, and gastric cancer. ( 37 , 38 , 39 ) Hu et al showed that the activity of ALDOA was increased under stimulation of phosphoinositide 3‐kinase–dependent activation of Rac by releasing filamentous actin‐bound ALDOA, linking actin remodeling to glycolysis. ( 40 ) Overexpression of ALDOA promoted formation of a cancer‐associated proton pump inhibitor with γ‐actin and accelerated lung cancer metastasis, ( 37 ) suggesting its role as an oncogene in tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…snoRNA ACA11 was reported to promote human hepatoma cell line Huh7 proliferation and EMT through the PI3K/AKT pathway 12. SNORD105b was overexpressed in gastric cancer tissues and induced tumorigenesis via ALDOA/C-Myc pathway 13. SNORA23 promoted pancreatic ductal adenocarcinoma cell proliferation and invasion, as well as tumor growth and metastasis, via inducing spectrin repeat-containing nuclear envelope 2 in mice 14.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially prominent in cancer as biopsies typically show altered expression of subsets of snoRNA genes [173][174][175] (for a review, see [176]) and have suggested their potential as diagnostic or prognostic markers [176]. Hence, several snoRNAs have been proposed as proto-oncogenes or tumor suppressors based on in vitro analyses [177][178][179][180][181]. They are also actors of other conditions, e.g., the Prader Willi syndrome (PWS) for the snord116 snoRNAs (for a review, see [182]), or the leukoencephalopathy with brain calcifications and cysts (LCC) for the U8 snoRNA [183].…”
Section: The Diversity Of C/d Snorna Expressionmentioning
confidence: 99%